2015
DOI: 10.1177/0011128715607534
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Immunity on Over-Dispersed Criminal Victimizations: Zero-Inflated Analysis of Household Victimizations in the NCVS

Abstract: This study aims to empirically test the immunity effect on the frequency distribution of household victimizations. To clarify the immunity effect, the statistical construction of zero-inflated models is reviewed and compared with that of non-zero-inflated models. The Benjamini and Hochberg correction is used to address the limitation of p values in multiple testing. Compared with the findings from the non-zero-inflated model, two sets of coefficients from the zero-inflated model reveal that there exist more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 66 publications
(151 reference statements)
4
29
0
Order By: Relevance
“…Both tables contain three models, which correspond to the hypotheses H1, H2, and H3, respectively. We find that the control variables exhibit patterns that are highly similar to those reported in several previous studies of victimization risk based on the NCVS (e.g., Lauritsen & Carbone-Lopez, 2011;Park & Fisher, 2017;Rezey, 2020;Xie & Baumer, 2018). For example, as the results for H1 in both tables 5 and 6 indicate, having higher income, owning a home, being older, being married, living outside of central cities, and living in the Northeast are all related to lower risks of violent and property victimizations.…”
Section: Difference In Victimization Rates By Citizenship Statussupporting
confidence: 86%
“…Both tables contain three models, which correspond to the hypotheses H1, H2, and H3, respectively. We find that the control variables exhibit patterns that are highly similar to those reported in several previous studies of victimization risk based on the NCVS (e.g., Lauritsen & Carbone-Lopez, 2011;Park & Fisher, 2017;Rezey, 2020;Xie & Baumer, 2018). For example, as the results for H1 in both tables 5 and 6 indicate, having higher income, owning a home, being older, being married, living outside of central cities, and living in the Northeast are all related to lower risks of violent and property victimizations.…”
Section: Difference In Victimization Rates By Citizenship Statussupporting
confidence: 86%
“…7.3). To determine the most adequate Poisson-based regression model for a dependent variable of interest, the mean and the variance of the Poisson distribution was examined using R. The result indicated that the frequency distribution of cyberbullying was more over-dispersed than expected by a random and independent Poisson distribution (Park & Fisher, 2017). This study, therefore, calculated negative binomial regression models to consider that the expected variances of cyberbullying exceeded the variance of the Poisson distribution.…”
Section: Methodsmentioning
confidence: 99%
“…When γ is given as 2, this function becomes the AIC statistics. If γ is equal to log(N), this function is identified as the BIC statistics, and if γ is identical to log((N + 2)/24), this function is equal to the ABIC statistics (Muthén & Muthén, 1998Park & Fisher, 2017). As these model-fit statistics control for the number of parameters, they can compare both nested and non-nested models (Dayton, 2003).…”
Section: Model-fit Test Of Semsmentioning
confidence: 99%